2001
DOI: 10.1002/rrr.648
|View full text |Cite
|
Sign up to set email alerts
|

Regional‐scale effects of flow regulation on lowland riverine fish communities in New South Wales, Australia

Abstract: Lowland reaches of 40 rivers in New South Wales, Australia, were designated as 'regulated' or 'unregulated', depending upon the degree to which flows were modified by the operation of a dam upstream. Five replicate rivers of each type were selected from the North Coast, South Coast, Darling and Murray regions in the State. Fish communities in each river were sampled in summer and winter in two consecutive years. Regulated and unregulated rivers contained significantly different fish communities, although commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(54 citation statements)
references
References 38 publications
3
50
0
1
Order By: Relevance
“…Native fish now make up only 20% of the total catch in regulated rivers in the MDB, as a result of changes in flow regulation disrupting the natural water-regime triggers for fish spawning, thermal pollution and barriers to movement (Gehrke et al 1995;Gehrke and Harris 2001;Growns 2008). The MDB's aquatic biodiversity has also been severely affected by barriers, cutting access to rivers, and flood levees, cutting access to floodplains, with more than 3600 weirs in the MDB that block longitudinal connectivity (Arthington and Pusey 2003).…”
Section: Impacts On Biodiversitymentioning
confidence: 99%
“…Native fish now make up only 20% of the total catch in regulated rivers in the MDB, as a result of changes in flow regulation disrupting the natural water-regime triggers for fish spawning, thermal pollution and barriers to movement (Gehrke et al 1995;Gehrke and Harris 2001;Growns 2008). The MDB's aquatic biodiversity has also been severely affected by barriers, cutting access to rivers, and flood levees, cutting access to floodplains, with more than 3600 weirs in the MDB that block longitudinal connectivity (Arthington and Pusey 2003).…”
Section: Impacts On Biodiversitymentioning
confidence: 99%
“…In their assessment of fish species, hydrology and macroinvertebrates, Davies et al (2010) found 20 of the 24 river basins to be in poor or very poor condition. The impacts of flow modifications, including thermal pollution, have been implicated in the demise of native fish in the MDB-regulated rivers, because of their impacts on physiology, spawning and movement (Gehrke and Harris 2001;Growns 2008). Native fish numbers are now only 10% of pre-European levels (MDBC 2004) because of factors such as changes to the natural flow regime, habitat degradation and barriers to biological connectivity (Pratchett et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Depuis les cinquante dernières années, une abondante littérature fait état de ces perturbations anthropiques et des impacts qu'elles ont eu sur l'écocomplexe alluvial en Europe (Pautou, 1984 ;Pautou et al, 1992 ;Décamps, 1993 ;Hughes, 1994 ;Piégay, 1995 ;Bravard et al, 1997 ;Surian, 1999 ;Piégay et al, 2003a ;Steiger et al, 2005), aux États-Unis (Johnson, 1994 ;Gurnell et Gregory, 1995 ;Miller et al, 1995 ;Johnson, 1998 ;Merritt et Cooper, 2000 ;Cooper et al, 2003) et en Australie (Brierley et al, 1999 ;Kingsford, 2000 ;Gehrke et Harris, 2001). Ces impacts anthropiques se traduisent le plus souvent par la suppression de la dynamique naturelle (Peiry, 1997), la simplification de la morphologie du chenal (Sidle et Sharma, 1986 ;Steiger et al, 2000 ;Pisùt, 2002), l'isolement du chenal principal de sa plaine d'inondation par diminution de la largeur du lit (Eschner et al, 1983) et le changement de physionomie de la plaine d'inondation (Johnson et al, 1992 ;Johnson, 1997).…”
Section: Introductionunclassified